Feasibility and safety study of wearable cyborg Hybrid Assistive Limb for pediatric patients with cerebral palsy and spinal cord disorders - Takahashi, Kazushi; Mizukami, Masafumi; Watanabe, Hiroki; Kuroda, Mayumi Matsuda; Shimizu, Yukiyo; Nakajima, Takashi; Mutsuzaki, Hirotaka; Kamada, Hiroshi; Tokeji, Kayo; Hada, Yasushi; Koseki, Kazunori; Yoshikawa, Kenichi; et al. (Frontiers in Neurology, 2023)
Introduction The wearable cyborg Hybrid Assistive Limb (HAL) is the world’s first cyborg-type wearable robotic device, and it assists the user’s voluntary movements and facilitates muscle activities. However, since the minimum height required for using the HAL is 150 cm, a smaller HAL (2S size) has been newly developed for pediatric use. This study aimed to (1) examine the feasibility and safety of a protocol for treatments with HAL (2S size) in pediatric patients and (2) explore the optimal method for assessing the efficacy of HAL. Methods This clinical study included seven pediatric patients with postural and motor function disorders, who received 8–12 sessions of smaller HAL (2S size) treatment. The primary outcome was the Gross Motor Function Measure-88 (GMFM-88). The secondary outcomes were GMFM-66, 10-m walk test, 2- and 6-min walking distances, Canadian Occupational Performance Measure (COPM), a post-treatment questionnaire, adverse events, and device failures. Statistical analyses were performed using the paired samples t-test or Wilcoxon signed-rank test. Results All participants completed the study protocol with no serious adverse events. GMFM-88 improved from 65.51 ± 21.97 to 66.72 ± 22.28 (p = 0.07). The improvements in the secondary outcomes were as follows: GMFM-66, 53.63 ± 11.94 to 54.96 ± 12.31, p = 0.04; step length, 0.32 ± 0.16 to 0.34 ± 0.16, p = 0.25; 2-MWD, 59.1 ± 57.0 to 62.8 ± 63.3, p = 0.54; COPM performance score, 3.7 ± 2.0 to 5.3 ± 1.9, p = 0.06; COPM satisfaction score, 3.3 ± 2.1 to 5.1 ± 2.1, p = 0.04. Discussion In this exploratory study, we applied a new size of wearable cyborg HAL (2S size), to children with central nervous system disorders. We evaluated its safety, feasibility, and identified an optimal assessment method for multiple treatments. All participants completed the protocol with no serious adverse events. This study suggested that the GMFM would be an optimal assessment tool for validation trials of HAL (2S size) treatment in pediatric patients with posture and motor function disorders.